Compensation schemes of motivating & attracting RnD scientists in Singapore. - Goh, Doris Sock Huang. (2013)
The importance of R&D as an instrument for restructuring Singapore’s economy is gaining recognition by the government. Over the last few years, the government has earnestly encouraged the growth ofR&D activities in all sectors of the economy. Besides support from the government, the very success of our R&D projects may be dependent on our ability to attract, motivate and retain world-class R&D scientists. Thus, the objective of our research is to evaluate the effectiveness of the compensation schemes in the public sector and the determinants of pay effectiveness. This report also attempts to refine these compensation schemes in order to meet the needs and wants of the scientists. In this way, we will be able to attract, motivate and retain R&D scientists, and R&D activities of higher quality can take place.